Emlékképek Fornet Béla professzor úrról és az I. sz. belklinikai otthonunkról - Hankiss, János (Gerundium, 2013)
Flashes of Memory: About Professor Béla Fornet and Our Home at the Clinic of Internal Medicine One. Retired internalist head physician, titular professor, and writer-doctor János Hankiss reminiscenses about his years spent in Debrecen. The guiding spirit of the clinic of internal medicine headed by Professor Béla Fornet was this: the patient comes first. Moreover, it is not the disease that has to be treated, the sick man has to be cured, at the highest possible level of science and at the same time with a humane attitude. Forms of refresher training, reading, scientific research are required to make treatment ever more efficient. The mode of presentation is unusual: it assumes the form of a dialogue, and concrete memories elicit distilled ideas.